Menggali Nilai Pancasila Dalam Tarian Raego Topo Uma Dengan Perspektif Filsafat Fenomenologis Armada Riyanto - Tonta, Rex Firenze; Pandor, Pius (Studi Budaya Nusantara, 2023)
The focus of this paper explores the values of Pancasila in the local wisdom of the Topo Uma community in Porelea village, Kec. Pipikoro, Kab. Sigi, Central Sulawesi. Specifically the Raego Dance, this is a dance performed by men and women in a circular formation while reciting verses in the old Uma language. The purpose of this paper is to explore whether the assumption that the values of Pancasila in the local wisdom of the Indonesian people are truly rooted and especially internalized by the Topo Uma community. The method used in this research is qualitative, with a phenomenological philosophical approach from the perspective of Armada Riyanto, which is obtained from the book Local Wisdom ~ Pancasila: The Items of Indonesian Philosophy, as well as in his book Relationality and Methodology. This phenomenological philosophical perspective contributes a phenomenological interpretation to describe the experience and appreciation of the Topo Uma community. The findings in this research, the saying that the values of Pancasila are alive and rooted in the local wisdom of the community is not just a slogan. In particular, the first precept, it was permeated and lived in the life of the Topo Uma community even before the entry of Christianity there as a designation for entities that transcend or overcome, namely; Karampue Langi, Karampue Tana or Topehila Ngkarawe Topejadi.